Intergovernmental Relations between BKKBN and DP3APPKB in Strengthening Male Family Planning Participation through the Arjuna Mesra Group in Surabaya - Okta Vema Kurniasari; Elsa Febriana; Revaneza Agung Sabrina Putri; Luna Winatasia (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
Male participation in Indonesia’s Family Planning program through vasectomy remains very low, reaching 0.1% in 2024, indicating persistent structural and socio-cultural constraints in reproductive health governance. This study analyzes intergovernmental collaboration between the National Population and Family Planning Agency (BKKBN) and the Surabaya City DP3APPKB in optimizing the Arjuna Mesra male family planning group using Wright’s (1988) Intergovernmental Relations framework. A qualitative literature review was conducted using 26 relevant sources published between 2014 and 2026, analyzed thematically based on five IGR dimensions.The findings show that collaboration operates through hierarchical coordination, PLKB-mediated field implementation, community-based mobilization, and fiscal support via the BOKB DAK scheme. However, program effectiveness is constrained by structural dependence on PLKB, limited adaptive feedback in intergovernmental coordination, and persistent socio-cultural resistance to male contraception. These constraints suggest that low male participation is shaped by both institutional design limitations and normative barriers rather than a single causal factor. The study recommends strengthening standardized yet adaptive community facilitation mechanisms, improving intergovernmental feedback systems, and integrating behavior change communication involving local leaders to support SDG 5.